2021
DOI: 10.3390/soilsystems5020033
|View full text |Cite
|
Sign up to set email alerts
|

Single and Binary Fe- and Al-hydroxides Affect Potential Phosphorus Mobilization and Transfer from Pools of Different Availability

Abstract: Phosphorus (P) fixation is a global problem for soil fertility and negatively impacts agricultural productivity. This study characterizes P desorption of already fixed P by using KCl, KNO3, histidine, and malic acid as inorganic and organic compounds, which are quite common in soil. Goethite, gibbsite, and ferrihydrite, as well as hydroxide mixtures with varying Fe- and Al-ratio were selected as model substances of crystalline and amorphous Fe- and Al-hydroxides. Especially two- and multi-component hydroxide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…that Fe and Al in the subsoil exert a major control of P through geochemical rather than biological cycling, this does not exclude a role of Fe-and Al-bound P for biological uptake, particularly not in P-rich sites. In this respect we hypothesize that ITM and other Al phases such as Al(OH)3, which dominate the P speciation in the B horizon of these boreal Podzols, are more likely sources for geochemically active P than Fe oxides, because of their lower thermodynamic stability under acid conditions (Gustafsson, 2001, Gypser et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…that Fe and Al in the subsoil exert a major control of P through geochemical rather than biological cycling, this does not exclude a role of Fe-and Al-bound P for biological uptake, particularly not in P-rich sites. In this respect we hypothesize that ITM and other Al phases such as Al(OH)3, which dominate the P speciation in the B horizon of these boreal Podzols, are more likely sources for geochemically active P than Fe oxides, because of their lower thermodynamic stability under acid conditions (Gustafsson, 2001, Gypser et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent long-term desorption study by Gypser et al (2019), utilizing competitive inorganic and organic anions to release adsorbed P from Fe-and Al-hydroxides, it was found that P desorption increased in the order CaCl2 < CaSO4 < humic acid < citric acid. A further desorption study by Gypser et al (2021) showed that goethite exhibited the highest desorption, followed by gibbsite and then ferrihydrite upon applying both organic and inorganic competitors. Furthermore, a joint experimental-theoretical approach by Kubicki and Ohno (2020) demonstrated that salicylate can replace adsorbed phosphate on the goethite surface.…”
Section: Introductionmentioning
confidence: 96%
“…Low molecular weight organic acids will release anions, such as P from the soil and are attributed to the desorption of inorganic anions and solubilization of P compounds which is achieved through complex formation between organic acids/anions. Low molecular weight organic acids have the ability to: (1) promote mineral dissolution, (2) modify pH and chemical equilibria in soil solution, (3) occupy ligand exchange sites, and (4) form complexes with Fe, Al, and Ca ions, thus inhibiting anion adsorption sites on soil particles (Gypser et al, 2021). Many research has looked at the role of low molecular weight organic acids in releasing phosphorus from soils, although it is uncertain how effective organic ac-ids are at solubilizing P from calcareous soils of different calcareousness (Mazinanian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%